2006
DOI: 10.1097/01.jom.0000183096.20678.f1
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Investigation of PM10 in Ambient Air and Cardiopulmonary Hospital Admissions in Allegheny County, Pennsylvania: 1995???2000

Abstract: Even at the lower levels of ambient air pollution as measured by PM10, there is still a suggestion of an adverse health effect in the elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 23 publications
0
13
1
Order By: Relevance
“…49 However, the effects seem to be stronger for older patients with even short-term exposures. 50 This study further revealed that the 1-hour, 24-hour and annual mean concentration for NO 2 are below the national standard. Evidence from the risk characterisation assessment shows a negligible risk for acute and intermediate exposure to ambient levels of NO 2 .…”
Section: Discussionmentioning
confidence: 56%
“…49 However, the effects seem to be stronger for older patients with even short-term exposures. 50 This study further revealed that the 1-hour, 24-hour and annual mean concentration for NO 2 are below the national standard. Evidence from the risk characterisation assessment shows a negligible risk for acute and intermediate exposure to ambient levels of NO 2 .…”
Section: Discussionmentioning
confidence: 56%
“…Topography, meteorology, and air pollution exacerbate the ambient air quality conditions of Zunyi, and the mountains of up to 1250 m in height that surround Zunyi inhibit the dispersion of air pollutants. In addition, consistent with several recent time series studies (27-29), we used the penalized spline model for our data analysis, whereas most previous temperature time series studies have been based on the GAM in S-PLUS.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found associations between air pollution and stroke hospital admissions [5][11], while other studies have reported no significant links [12][16]. Moreover, most studies have been conducted in North American and European cities [5][7], [9], [13], [14], [17] with only limited information from Asia [8], [12], [18].…”
Section: Introductionmentioning
confidence: 99%